Environmental Cost in Indonesia Spillover Effect Between Consumption and Production - Pirmana, Viktor; Alisjahbana, Armida Salsiah; Yusuf, Arief Anshory; Hoekstra, Rutger; Tukker, Arnold (Frontiers in Sustainability, 2021)
Reducing environmental costs is a significant concern for Indonesia's future. This paper explores Indonesia's environmental costs from emissions and forest resources and identifies the priority sectors in terms of economic and environmental performance. We use environmentally extended input-output analysis (EEIO) for calculating the environmental costs and further extension with linkages analysis to identify the priority sectors. The study finds that the total environmental costs of emissions due to final demand is around 7 % of GDP. This environmental cost is significantly due to domestic products, with household consumption being the largest contributor. The top ten sectors in the Indonesian economy are responsible for about 70% of the total environmental costs of emissions. Based on pollutants source, SOx, NOx, CO2, and CH4 contribute more than half of emissions' ecological costs. We also find that forest resources' environmental cost is only 7.5% of the total environmental cost. Lastly, this study finds that key sectors of economic and sustainability points of view are textile manufacturing; publishing, printing, and reproduction of recorded media; chemicals n.e.c; manufacture of other non-metallic mineral products; Construction; other land transport. Finally, this paper discusses the policy options for Indonesia to promote sustainable consumption and production in terms of reducing environmental costs while managing economic development.